Compensation of a hybrid platform dynamics using wave energy converters in different sea state conditions - Gaspar, J.F.; Kamarlouei, M.; Thiebaut, F.; Guedes Soares, C. (Renewable energy, 2021)
An hybrid floating platform concept, combining a wind turbine with wave energy converter devices, has been proposed. This paper conducts a further exploration of these synergies analyzing the utilization of the wave energy converters to assist the platform water ballast system on the compensation for variations on the sea state conditions. An experimental campaign has been performed for a preliminary evaluation of this approach. It is limited, for simplification, to five different sea state conditions in head wave situation. However, it allows the study of the main design principles that should be followed to develop the approach in a more complex scenario. The experimental results indicate that energy wave converters assist the water ballast system in the tested sea state conditions, and even extend the operational sea state range. Moreover, it indicates that wave energy converters located at downwind and upwind sides of the platform have different roles in the compensation of the platform dynamics. The first ones are dedicated to the production of platform restoring moments while the seconds are harvesting the power that should be supplied to the downwind of the wave converters. The case study considers the application of oil-hydraulic technology in wave energy converters. •WECS are used to increase the platform resistance to fast changes in the wind.•An experimental campaign has been performed for evaluation of this approach.•The results indicate that it may replace the water ballast approach.•WECS located at downwind and upwind sides have different roles in the stabilization.